1985
DOI: 10.1111/j.1468-2958.1985.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Information and Employee Anxiety About Organizational Change

Abstract: Studies of job attitudes hove traditionally been conducted on the correspondence between individuol needs and objective job chorocterisiics. A recently developed theory, however, suggests thotjob ottitudes may be o function ofsocialinformotion received (Soloncik & Pfeffer, 1978). This investigation used social informotion processing theory as the bosis for ostudy of antecedents to employee onxiety about o move to on open office environment. The structural equation model developed from social information proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 19 publications
(30 reference statements)
4
107
0
7
Order By: Relevance
“…Timely and detailed information seems a critical element of any change endeavor. This may be due to the anxiety/uncertainty reducing effect that information about the pending changes may have on employees (Ashford, 1988;Miller & Monge, 1985). We expect that change information will facilitate adaptive attitudes (willingness to change) as well as behavioral change (adaptive behavior).…”
Section: Employee Adaptability: Change Resourcesmentioning
confidence: 99%
“…Timely and detailed information seems a critical element of any change endeavor. This may be due to the anxiety/uncertainty reducing effect that information about the pending changes may have on employees (Ashford, 1988;Miller & Monge, 1985). We expect that change information will facilitate adaptive attitudes (willingness to change) as well as behavioral change (adaptive behavior).…”
Section: Employee Adaptability: Change Resourcesmentioning
confidence: 99%
“…For example, Miller and Monge (1985) found that the provision of information was associated with lower levels of anxiety for 146 employees about to relocate to a new building that would have significant implications for their work practices. Brockner, DeWitt, Grover, and Reed (1990) found that better reactions to job redundancies were observed when information about why resources were allocated in particular ways was provided to employees.…”
mentioning
confidence: 99%
“…The change literature has also emphasized the psychological discomfort associated with uncertainty. For instance, Miller and Monge (1985) found that uncertainty was related to anxiety. Schweiger and Denisi (1991) found that uncertainty had a moderate correlation with stress, averaging around .30 across several time periods.…”
mentioning
confidence: 99%